Is integrated multitrophic aquaculture the solution to the sectors' major challenges? – a review. (3rd February 2015) - Granada, Luana; Sousa, Nádia; Lopes, Sofia; Lemos, Marco F. L.
Abstract: The growing demand for fish products and the dwindling productivity of marine fish stocks due to the overexploitation of fisheries place the aquaculture industry as a key contributor to the global fish supply. The intensive development of aquaculture has raised a range of environmental concerns such as effluent discharge, excessive use of resources and dependence on commercial feed. In this context, the development of sustainable aquaculture systems is becoming the cornerstone for long‐term aquaculture expansion, and to achieve environmental sustainability. Integrated multitrophic aquaculture (IMTA) is regarded as a suitable approach to limit aquaculture nutrients and organic matter outputs through biomitigation. The cocultured species are used as biofilters, and each level has its own independent commercial value, providing both economic and environmental sustainability. Here, environmental issues of aquaculture and the current status of IMTA are reviewed and its future prospects discussed. Also, the opportunities to expand this systems' complexity with increased added‐value and trophic levels are introduced.